Moral Value Of Film “Ketika Cinta Bertasbih” Written by Habiburrahman El Shirazy - Muhammad Zidan; Marudut Bernadtua Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2022)
Ketika Cinta Bertasbih is a film based on the phenomenal novel written by Habiburrahman El-Shirazy. Ketika Cinta Bertasbih itself tells the story of a young Indonesian named Khoirul Azzam, who is a student who is criticizing education in Egypt. This film tells the struggle of an Azzam in completing his studies as well as being the backbone for his family. Ketika Cinta Bertasbih itself does not only focus on Azzam's struggles but also tells his love story which must be hindered by social and economic status. The film Ketika Cinta Bertasbih is a film with an Islamic nuance, so there are many moral messages that can be learned. The author will examine the film Ketika Cinta Bertasbih by using a qualitative approach with a descriptive method. The author uses primary and secondary data, where primary data is taken from the analysis of films which watched repeatedly, while secondary data is taken via the internet. The author watches the film Ketika Cinta Bertasbih then pays attention to the movements and conversations of the players, then the data is analyzed so that it can be presented in this paper.